Closed-form solutions of generalized linear first-order differential equations by Picard’s method - de Castro, Antonio S. [UNESP] (FapUNIFESP (SciELO), 2024)
For homogeneous linear first-order differential equations, it is shown that Picard’s method of successive approximations is effective to furnish a closed-form solution even if the coefficient is an arbitrary function.
Soluções em forma fechada de equações diferenciais lineares de primeira ordem generalizadas pelo método de Picard
Keywords: equação diferencial de primeira ordem; first-order differential equation; Método de Picard; Picard’s method; successive approximations; sucessivas aproximações